PENGARUH KARAKTER EKSEKUTIF, KOMITE AUDIT, UKURAN PERUSAHAAN, LEVERAGE, SALES GROWTH DAN PROFITABILITAS TERHADAP TAX AVOIDANCE (Survei Pada Kantor BEI Di Semarang Tahun 2011-2013) - Desi Nurhayati, 12.05.52.0050; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2016)
The study examined the influence of executive character, the audit committee, company size, leverage, sales growth and profitability against tax avoidance. This research was conducted at the Indonesian Stock Exchange by using analysis unit manufacturing companies that have gone public.Â The sampling method using purposive sampling the study period of 2011 up to 2013. The relationship and influence between variables or described by using multiple regression analysis.Â The results showed that the character of executives, audit committee, and Profitability has no effect on tax avoidance while the size of the company and Payable, Sales Growth effect on tax avoidance.Keywords: Character Executives, Audit Committee, Company Size, Leverage, Sales Growth, Profitability, Tax Avoidance